Pleural effusion in severe aortic stenosis: marker of an adverse haemodynamic constellation and poor prognosis - Alexander Breuss; Maximilian Porsch; André Aschmann; Lukas Weber; Sharon Appert; Philipp K. Haager; Daniel Weilenmann; Simon Wildermuth; Hans Rickli; Micha T. Maeder (ESC Heart Failure, 2024)
Abstract Aim Pleural effusion (PE) is a common chest radiography (CXR) finding in patients with advanced cardiac disease. The pathophysiology and clinical value of PE in this setting are incompletely defined. We aimed to assess the haemodynamic correlates and prognostic impact of PE in patients with severe aortic stenosis (AS). Methods and results We studied 471 patients (mean age 74 ± 10 years) with severe AS (indexed aortic valve area 0.42 ± 0.12 cm2/m2, left ventricular ejection fraction 58 ± 12%) undergoing right heart catheterization and upright CXR prior to aortic valve replacement (AVR). Two radiologist independently evaluated all CXR for the presence of bilateral PE, unilateral, or no PE, blinded to any other data. There were 49 (10%) patients with bilateral PE, 32 (7%) patients with unilateral PE, and 390 (83%) patients with no PE. Patients with bilateral PE had the highest mean right atrial pressure, mean pulmonary artery wedge pressure (mPAWP), and pulmonary vascular resistance, and had the lowest stroke volume index while those with unilateral PE had intermediate values. In the multivariate analysis, mPAWP was an independent predictor of any PE and bilateral PE. After a median (interquartile range) post‐AVR follow‐up of 1361 (957–1878) days mortality was highest in patients with bilateral PE (2.7 times higher than in patients without PE), whereas patients with unilateral PE had similar mortality as those without PE. Conclusions In severe AS patients, the presence of PE, particularly bilateral PE, is a marker of a poor haemodynamic constellation. Bilateral PE is associated with a substantially increased post‐AVR mortality.